Preeclampsia: A Review of Early Predictors. Issue 3 (5th July 2021) - Abbas, Riwa A.; Ghulmiyyah, Labib; Hobeika, Elie; Usta, Ihab M.; Mirza, Fadi; Nassar, Anwar H.
Abstract : Abstract: Preeclampsia is a progressive, multi-system disorder of pregnancy associated with morbidity and mortality on both the mother and the fetus. Currently, research is directed at identifying early biomarkers of preeclampsia in order to predict its occurrence. This is important because it helps understand the pathophysiology of the disease, and thus, promises new treatment modalities. Although a clear understanding of the pathogenesis of PE remains elusive, the currently most accepted theory suggests a two-stage process. The first stage results in inadequate remodeling of the spiral arteries and leads to the second stage, whereby the clinical features of the syndrome are featured. In this review, we summarize the modalities that have been studies so far to predict preeclampsia. The use of uterine artery Doppler and several other biomarkers such as vitamin D, soluble fms-like tyrosine kinase 1/placental growth factor (sFLT1/PlGF) ratio, soluble endoglin, and a subset of T-lymphocytes has shown promising results. We are still at early stages in this advance, and no clear recommendations have been made about their clinical use to date. Further studies are still needed to improve screening strategies and evaluate the cost-effectiveness of any intervention.